A study of the feasibility of implementing a coffee proccessing and marketing plant in the municipality of 24 de Mayo - Márquez Bravo, Yesenia Johana (2017)
This study aimed at evaluating the market, technical and economic feasibility of a coffee processing plant under the administrative framework of the Asociación 24 de Agosto, an organization dedicated to buying and selling coffee beans. We conducted a market study through surveys directed to a sample of the economically active population in the municipalities of Portoviejo, Manta, Chone and 24 de Mayo, in the province of Manabí. In addition, we carried out in-situ observations to identify the current capabilities for processing coffee beans, including raw material availability, supply and demand, processing and techniques necessary for making soluble coffee, efficiency and financial capacity, and consumers ́ expectations. Our data served to determine the necessary initial investment, which was estimated to be $307 871.75, including infrastructure costs and labor capital with 86.78% of the project financed with a loan and the remaining 13.22 % with own capital. The plant will be able to process 115 200 kilograms of coffee beans, and the recovery time was esti- mated to be 3 years, with a rate of 21.33%. The results of our technical, economic and market study showed a consumption rate of 88%, with a preference towards the soluble presentation (96%) and a monthly purchase frequency of 68%. These values demonstrated that the coffee bean processing plant is feasible, and has the potential to be a generator of jobs, supporting the local economy and agroindustrial growth for a change in the productive matrix.